Case Report: A Case of Unusual Combination of Hypothyroidism, Myocardial Bridging, and Myocardial Infarction-Induced Left Ventricular Aneurysm - Li, Yueliang; Liu, Zhengjiang (Frontiers in Cardiovascular Medicine, 2021)
Background: Myocardial bridging (MB) of the coronary artery is a congenital anatomical variation, which has traditionally been considered a benign condition that does not cause cardiovascular events. However, recent studies have shown that MB is associated with major adverse cardiac events, including angina, myocardial infarction, arrhythmia, syncope, and even sudden death. Case: We report a case of a 41-year-old man who had hypothyroidism and MB associated with ventricular aneurysm following myocardial infarction. This patient was admitted to our hospital because of 11 days of sudden discomfort and pain in the chest. An electrocardiogram on admission showed an old myocardial infarction. Coronary angiography showed MB in the distal segment of the left anterior descending artery. Left ventricular angiography, which was performed using a pigtail catheter, showed ventricular aneurysm formation. Thyroid ultrasound demonstrated hypothyroidism and Hashimoto's thyroiditis. Patients with hypothyroidism and MB have a high risk of acute myocardial infarction or even sudden death. Conclusion: Observations in our case suggest that early recognition of hypothyroidism and MB is important for risk stratification and prognosis in patients with myocardial necrosis and acute coronary syndrome. Additionally, this early recognition may have positive effects on cardiovascular outcomes in patients with hypothyroidism.